Lipid and carotenoid metabolism in the developing embryos of the intertidal anomuran crab, Emerita asiatica (Milne Edwards). Issue 3 (3rd July 2019) - Persia Jothy, T; Rajesh Kannan, R; Subramoniam, T
ABSTRACT: Lipids and lipid-soluble carotenoids play a pivotal role in the embryonic development of decapod crustaceans. The present study describes the progressive changes in the lipid and carotenoid composition of the embryos of the intertidal anomuran crab, Emerita asiatica during development. Major lipid classes in the embryos include triglycerides (TG), phospholipids and cholesterol which show a steady decrease during embryogenesis. Utilization of TG results in the release of free fatty acids (FFA) that constitute ultimate source for energy metabolism during embryogenesis. The important fatty acids are Saturated fatty acids (SFA) 16:0 and 18:0, Monounsaturated fatty acids (MUFA) 16:1n7 and 18:1n9, and the polyunsaturated fatty acids (PUFA) 20:5n3 and 22:6n3. MUFA are used at a higher rate (66%) than SFA (58%) and PUFA (56%). The decline in the cholesterol level especially during later part of embryogenesis could be related to its utilization as precursor in the de novo synthesis of ecdysteroids by the developing Y organ. Steady decline of phospholipid during embryonic development suggests its role in the formation and stabilization of cellular membrane structures. Glycolipids, conjugated to lipovitellin, showed a significant decline during embryogenesis. E. asiatica eggs accumulate carotenoid pigments such as β-carotene and astaxanthin, along with canthaxanthin showed significant fluctuations. In crustaceans, carotenoids form the precursors in eye pigments and chromatophores formation.